2005
DOI: 10.1557/proc-872-j18.6
|View full text |Cite
|
Sign up to set email alerts
|

Towards Novel Light-Activated Shape Memory Polymer: Thermomechanical Properties of Photo-responsive Polymers

Abstract: The basic principle for the operation of a thermally stimulated shape memory polymer (SMP) is a drastic change in elastic modulus above the glass transition temperature (T g ). This change from glassy modulus to rubbery modulus allows the material to be deformed above the T g and retain the deformed shape when cooled below the T g . The material will recover its original shape when heated above the T g again. However, thermal activation is not the only possibility for a polymer to exhibit this shape memory eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 5 publications
0
13
0
Order By: Relevance
“…SMPs change their shape when a particular stimulus is applied such as light [181], heat [182], electric field [183], magnetic field [184], sonic field [185], solvent ions [186], pH value [187], specific antigen-antibody interactions [188] and others. Due to this unique feature, they are successfully applied as smart medical devices [189,190], thermal sensors and actuators [191][192][193], and smart textiles [194]. In 2005, Lendlein et al have reported an approach of introducing photosensitive functional groups into a polymer matrix to prepare optically triggered SMPs [195].…”
Section: Shape-memory Polymers With Coumarin As Reactive Moietymentioning
confidence: 99%
“…SMPs change their shape when a particular stimulus is applied such as light [181], heat [182], electric field [183], magnetic field [184], sonic field [185], solvent ions [186], pH value [187], specific antigen-antibody interactions [188] and others. Due to this unique feature, they are successfully applied as smart medical devices [189,190], thermal sensors and actuators [191][192][193], and smart textiles [194]. In 2005, Lendlein et al have reported an approach of introducing photosensitive functional groups into a polymer matrix to prepare optically triggered SMPs [195].…”
Section: Shape-memory Polymers With Coumarin As Reactive Moietymentioning
confidence: 99%
“…Light as a stimulus is exclusively efficient as it is easily available in the environment and does not include the use of seconday source of energy such as heat, electricity, or magnetic field, and hence it is environmental friendly. Light-active polymers have been proposed to be used in bioseparation (Wang et al, 2008), spring-lock truss elements for large boom structures, solar sails, morphing skins of aircrafts (Havens et al, 2005;Snyder and Tong, 2005;Dietsch and Tong, 2007), remotely triggered drug delivery systems (Wischke et al, 2009), cardiovascular therapeutic device (Maitland et al, 2002;Small et al, 2005b,c;Yakacki et al, 2007), medical stents (Small et al, 2005b(Small et al, ,c, 2007Lendlein, 2006), recordable and erasable memories (Kamenjicki et al, 2003, microrobots in medicine or optical microtweezers (Yu and Ikeda, 2005), optical storage (Chen et al, 2008), valves and switches in microdevices (Ikeda et al, 2003;Yu et al, 2003;Lendlein et al, 2005b;Jiang et al, 2006), and light-modulators and display devices (Akashi et al, 2002).…”
Section: Light-active Polymeric Hydrogelsmentioning
confidence: 99%
“…Light-activated shape memory polymer (LaSMP) is a special kind of SMPs. LaSMP realizes the shape memory function through reversible photochemical reactions structures (Lendlein et al, 2005;Snyder and Tong, 2005). The photochemical reactions occur with the stimulus of ultraviolet lights and do not generate heat (Jin et al, 2011).…”
Section: Introductionmentioning
confidence: 99%